ASSESSING THE RELATIONSHIP BETWEEN PRENATAL MENTAL HEALTH DISORDERS AND INFANT BONDING POSTPARTUM (The Research of Medical Science Review, 2024)
This study examines the relationship between prenatal mental health disorders and postpartum infant bonding among mothers at Swat Medical College and Allied Teaching Hospitals from 2022 to June 2024. A cohort of 250 pregnant women was assessed for prenatal mental health conditions, including anxiety and depression, using standardized diagnostic tools. Postpartum, maternal-infant bonding quality was evaluated through validated bonding scales at 6 weeks and 6 months after birth. Findings indicate that prenatal mental health disorders significantly affect maternal bonding with infants, with higher rates of bonding difficulties observed in mothers with diagnosed prenatal mental health conditions (p < 0.05). This research highlights the need for mental health interventions during pregnancy to support maternal-infant bonding and optimize infant developmental outcomes.